A Multi-Objective Facility Coverage Location Problem for Emergency Medical Service Decisions in Hajj - Huda Zaki Naji; Mohanad Al-Behadili; Mohammad Sari Kadim (مجلة بغداد للعلوم, 2024)
This paper proposes a multi-objective facility model of coverage location problem to determine the number, locations, and redeployments of Emergency Medical Services (EMS) system. The EMS runs with two types of ambulances, Basic Life Support (BLS) and Advance Life Support (ALS). The suggested Multi-objective Coverage Location model (MO-CL) considers a bi-objective function, which is minimizing the EMS costs and the fatigue of EMS crew members. This can be managed by reducing the number of redeployments for both types of ambulances while still providing the required coverage levels. The MO-CL model is based on the approximation hypercube model that eliminates the assumptions of autonomous ambulance operation and system-wide busy probability. It can be solved by applying a modified MO-CL search algorithm. The model and solution method have been applied for a case study based on real data collected from the Al Noor Specialist Hospital in Makkah, Saudi Arabia during the period of fifteen days of Hajj pilgrimage. The results showed that, to achieve the 95% coverage threshold of critical and non-critical demand, the MO-CL model needs at least 64 ambulances (29 ALS, 12 for BLS backups, and 23 for BLS) and 19 redeployments for every day (9 for ALS, 2 for BLS backup, and 8 for BLS).